Pseudotumour cerebri in children: Etiological, clinical features and treatment modalities - (:unkn) unknown (ELSEVIER SCI LTD, 2012)
To investigate the etiological and clinical features of pseudotumour cerebri (PTC) in children, features of 12 children with PTC were documented. The etiology could be clarified in 6 patients. The other 6 patients were accepted as idiopathic intracranial hypertension (primary PTC). Acetazolamide was used as the first drug and was effective in only 4 patients who had no underlying cause. Repeated lumbar punctures (LP) were performed in 6 patients and 5 of them were unresponsive. Prednisone was used in 3 patients and was effective in only one patient. The CSF pressure continued to be high in five patients and could be normalized only by withdrawing of the precipitating drug in three patients and by ventricular-peritoneal shunting in two patients with cerebral venous thrombosis. Although, medical treatment and repeated LP are usually effective in children with PTC, clarifying and solving the underlying cause can be crucial (C) 2011 European Paediatric Neurology Society. Published by Elsevier Ltd. All rights reserved.
Keywords: Pseudotumour; Idiopathic intracranial pressure; Child; IDIOPATHIC INTRACRANIAL HYPERTENSION; TRANS-RETINOIC ACID; PAPILLEDEMA; DIAGNOSIS; DISEASE; POPULATION; PRESSURE; CRITERIA